An Experimental Investigation of Risk Sharing and Adverse Selection - Franziska Tausch; Jan Potters; Arno Riedl (Center for Economic Studies and ifo Institute (CESifo), 2013)
Does adverse selection hamper the effectiveness of voluntary risk sharing? How do differences in risk profiles affect adverse selection? We experimentally investigate individuals' willingness to share risks with others. Across treatments we vary how risk profiles differ between individuals. We find strong evidence for adverse selection if individuals risk profiles can be ranked according to first-order stochastic dominance and only little evidence for adverse selection if risk profiles can only be ranked on the basis of second-order stochastic dominance. We observe the same pattern also for anticipated adverse selection. These results suggest that the degree to which adverse selection erodes voluntary risk sharing arrangements crucially depends on the form of risk heterogeneity.
Keywords: D81; C91; 330; adverse selection; risk sharing; experiments; risk heterogeneity